Assessment of the toxic effects of levetiracetam on biochemical, functional, and redox parameters of salivary glands in male Wistar rats - Fiais, Gabriela Alice [UNESP] (2023)
Levetiracetam (LEV) is an anticonvulsant for epilepsy. The toxic effects of this medication in tissues have been associated with redox state imbalance, which can lead to salivary gland dysfunction. Therefore, the current work investigated the effects of LEV on the biochemical, functional, and redox parameters of the parotid and submandibular glands in rats. For this, male Wistar rats (Rattus norvegicus albinus) were randomly divided into 3 groups (n = 10/group): Control (0.9% saline solution), LEV100 (100 mg/kg), and LEV300 (300 mg/kg). After 21 consecutive days of intragastric gavage treatments, pilocarpine stimulated saliva secretion was collected for salivary biochemical analysis. The extracted salivary glands were utilized for histomorphometry and redox state analyses. Our results showed that LEV300 increased plasma hepatotoxicity markers and reduced salivary amylase activity and the acinar surface area of the parotid gland. Total oxidant capacity and oxidative damage to lipids and proteins were higher in the parotid gland, while total antioxidant capacity and uric acid levels were reduced in the submandibular gland of the LEV100 group compared to Control. On the other hand, total oxidant capacity, oxidative damage to lipids and proteins, total antioxidant capacity, and uric acid levels were lower in both salivary glands of the LEV300 group compared to Control. Superoxide dismutase and glutathione peroxidase activities were lower in the salivary glands of treated animals compared to Control. In conclusion our data suggest that treatment with LEV represents a potentially toxic agent, that contributes to drug-induced salivary gland dysfunction.